2017
DOI: 10.1002/etc.3724
|View full text |Cite
|
Sign up to set email alerts
|

Mixture toxicity of phostebupirim and cyfluthrin: Species‐specific responses

Abstract: Currently, the potential impact of insecticide mixtures to nontarget organisms is largely unknown, and additional study is needed. The present study investigated the mixture toxicity of the organophosphate insecticide phostebupirim and the pyrethroid insecticide cyfluthrin using 4 nontarget species including Daphnia magna, Hyalella azteca, Pimephales promelas (fathead minnow), and Danio rerio (zebrafish). For each species, the toxicity of equipotent mixtures was compared with the expected toxicity estimated us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…This tool hts ecotoxicity data to the conceptual models (CA or IA) and then évaluâtes if there are any déviations for synergism/antagonism or dose level or ratio dependencies (i.e., depending on low or high doses, or dépendent on the ratio of the Chemicals in the mixture, respectively). In the same way, the Model Déviation Ratio (MDR) technique is used to détermine the biological signihcance and reproducibility of observed mixture effects (e.g., Belden et al 2007;Lopez Aca et al 2018;De Perre et al 2017;Belden and Brain 2018;Lanteigne et al 2015) by comparing predicted and observed results of mixture toxicity. If the MDR values are < 5, then the CA model applies since the additive MoA can be assumed.…”
Section: Ixture Modelsmentioning
confidence: 99%
“…This tool hts ecotoxicity data to the conceptual models (CA or IA) and then évaluâtes if there are any déviations for synergism/antagonism or dose level or ratio dependencies (i.e., depending on low or high doses, or dépendent on the ratio of the Chemicals in the mixture, respectively). In the same way, the Model Déviation Ratio (MDR) technique is used to détermine the biological signihcance and reproducibility of observed mixture effects (e.g., Belden et al 2007;Lopez Aca et al 2018;De Perre et al 2017;Belden and Brain 2018;Lanteigne et al 2015) by comparing predicted and observed results of mixture toxicity. If the MDR values are < 5, then the CA model applies since the additive MoA can be assumed.…”
Section: Ixture Modelsmentioning
confidence: 99%
“…Furthermore, compounds that affect specific organisms or sensitive life-stages and compounds known to interact with highly conserved targets across taxas e.g. pharmaceuticals, may also represent a special concern (de Perre et al, 2016;Jager et al, 2016;Vasquez et al, 2014). Under this perspective, it is evident that there is no "one-size-fits-all" ecotoxicological bioassay that can be used to comprehensively assess the effects of complex mixtures of chemicals in the environment.…”
Section: Complex Exposure Scenariosmentioning
confidence: 99%